ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KABUPATEN SIDRAP - Hamrullah, Hamrullah; Fitriani, Fitriani; Qurahman, Nur (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Economic growth is the process of changing a country's economic conditions continuously towards better conditions during a certain period. An economy is said to experience a change in its development if the level of economic activity is higher than that achieved in the previous period. The purpose of this study is to find out the factors that affect economic growth in Sidrap Regency. The design of this study is qualitatively descriptive. The types of data used in this study are quantaotative data and qualitative data. The data sources used are documents, individuals, and places. The data collection techniques used are field studies and data that is already available (skunder data).